Pengaruh Penerapan Model Pembelajaran Problem Based Learning Berbantuan QR-Code Terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran Pendidikan Pancasila - Elwijayanti, Wavi; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2024)
Critical thinking skills are one of the abilities that must be possessed by students to face life in the 21st century. This study aims to determine whether or not there is an effect of the Problem Based Learning learning model assisted by Qr-Code on students' critical thinking skills. The results of this study indicate that the implementation of learning with the implementation model of the Problem Based Learning learning model assisted by Qr-Code is able to improve students' critical thinking skills. This is evidenced by the observation data of the implementation of learning in the experimental class of 92.5% with a very good category. The results of the average value of the critical thinking ability test obtained by the experimental class received a value of 80. Based on the results of the paired sample t-test hypothesis test, it can be seen that the sig value. (2-tailed) experimental class and control class with a sample size of 32 people for each class is 0.000 for the experimental class and 0.001 for the control class. Because 0.000 and 0.001 <0.05, Ha is accepted and H0 is rejected. So, it can be said that there is an effect of the problem-based learning model assisted by QR-Code on the critical thinking skills of Class XI SMA Labschool Unesa 1 Surabaya City.